Healthcare utilisation: a mixed-method study among tea garden workers in Indian context - Sonalee Rajput; Sibasis Hense; K.R. Thankappan (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - The study examined the utilisation patterns of healthcare services among tea garden workers and analysed the factors influencing utilisation in an Indian context. Design/methodology/approach - The authors employed a mixed-method approach and an explanatory sequential design for the study. A survey was conducted in the beginning followed by in-depth interviews in a north-eastern state of India (Assam). Andersen health behaviour model was used to explore the factors influencing healthcare utilisation. The sample size for the survey and in-depth interviews were 300 and 19, respectively, recruited employing multistage random and purposive sampling techniques. Findings - Out of 300 workers surveyed, 169 (56.3%) were females, 257 (85.7%) were married, 77 (25.7%) were illiterates and 229 (76.3%) had monthly household income less than 100 US$. The survey also found that 47.3% and 15.3% had non-communicable and communicable disease respectively. Most of the workers (67.3%) utilised government facilities, and close to one third (28.7%) utilised tea garden hospitals. About 63.3% had health insurance, but a majority (78.9%) did not use it previously. The analyses of interviews explored the need, enabling, predisposing factors under three important themes influencing utilisation of healthcare services among the workers. Practical implications - The study generates evidence to strengthen the Indian Plantation Labour Act, 1951 for tea garden worker's welfare protection and warrants transition from colonial-era policies to contemporary industry realities in order to improve their living, employment, nutritional and health conditions. Originality/value - The research adds to the existing literature on overall healthcare services utilisation (including coverage and utilisation of health insurance) among blue collar workers who usually lack access to healthcare facilities and explores important factors that determine utilisation in the Indian context.